Reduced graphene oxide embedded polymeric nanofibers for thermo- responsive drug delivery systems - Sancar, Tugay. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In recent years, nanofibers have become popular in biomedical applications because of their distinctive qualities, such as the large surface area to volume ratio, porosity, and appreciable mechanical strength. Electrospinning is the most widely utilized method to manufacture nanofibers due to its straightforward setup and cost-effective production. Fabricated nanofibers can be modified with different functional groups to impart characteristic properties and enable their application. In recent years, ‘click’ chemistry transformations have been preferred to functionalize nanofibers. In this thesis, clickable copolymers were synthesized to generate furan functionalized polymeric nanofibers with the help of electrospinning. Morphological features of the produced nanofibers were characterized with SEM. Reduced graphene oxide (r-GO) was embedded into the nanofiber during electrospinning to provide a photothermal property to the fibrous material. Irradiation of r-GO- containing materials with near-infrared (NIR) light results in the conversion of the light into heat and increases the temperature of the surface of the fibrous substrate. Doxorubicin (DOX) was modified with a maleimide functional group to enable Diels-Alder (DA) cycloaddition between furan- functionalized nanofibers and maleimide-modified drug molecules. After successfully conjugating the drug molecule, exposing drug conjugated nanofiber to NIR light leads to retro Diels-Alder (rDA) reaction resulting in drug release thanks to rapid light-to-heat conversion.
Keywords: Nanofibers.; Biomedical materials.; Polymers in medicine.; Drug delivery systems.